Trust-building in a coopetitive multi-supplier network. Issue 2 (3rd June 2019) - Järvinen, Markus
Abstract : Purpose: Alliances are an important form of cooperation in the contemporary world. Although most of the different alliances have been rigorously studied, one type of alliance has been neglected: a multi-supplier network forcing potential competitors to cooperate. The purpose of this kind of network is to develop and maintain complex technological systems, such as ICT systems for the public sector. The coopetitive nature of the network poses numerous difficulties for productivity. This paper aims to explore how trust-building can mitigate such difficulties. Design/methodology/approach: The data were gathered via 16 semi-structured interviews and analyzed using data-driven content analysis. The respondents were representatives of the private and public sectors in Finland, tasked with building an ICT system for the Finnish Defense Forces in a multi-supplier network. Findings: The paper found that trust-building is influenced by structural and functional factors. For example, roles and responsibilities emerged as an important structural factor, and communication was seen as a crucial functional factor. Practical implications: The paper identifies factors that have to be managed properly for a multi-supplier network to function effectively and efficiently. Originality/value: The paper positions the multi-supplier network within the alliance framework. It also contributes to the literature on trust by identifying factors that influence trust-building.